A Cluster of Cefepime-induced Neutropenia During Outpatient Parenteral Antimicrobial Therapy. (11th February 2019) - Foong, Kap Sum; Hsueh, Kevin; Bailey, Thomas C; Luong, Lan; Iqbal, Ayesha; Hoehner, Christine; Connor, Lee; Casabar, Ed; Lane, Michael; Burnett, Yvonne; Ritchie, David; Krekel, Tamara; et al.
Abstract: A cluster of cefepime-induced neutropenia (CIN) was identified from June 2017 to May 2018 in a regional outpatient parenteral antimicrobial therapy population. Our data suggest prolonged courses of cefepime (≥2 weeks), administered by rapid intravenous push, were associated with a higher risk of CIN.